Layer-by-layer deposition of green synthesised silver nanoparticles on polyester air filters and its antimicrobial activity - Ekarat Detsri; Kanrayasiri Kamhom; Duangkamol Ruen-ngam (My University, 2016)
Silver nanoparticles stabilised with anionic polymeric polyelectrolytes were successfully synthesised by high-energy UV reduction. Three types of polyelectrolytes were used including poly(methacrylic acid) (PMA), poly(acrylic acid) (PAA) and poly(4-styrenesulphonic acid-co-maleic acid) (CoPSS). The formation of the prepared solutions exhibited surface plasmon resonance at the wavelength of 475, 730 and 408 nm by using PMA, PAA and CoPSS as the stabilising agents. UV–visible spectrophotometer, transmission electron microscope (TEM) and zeta potential analyser were employed to characterise the formation of the prepared solutions. The silver nanoparticles stabilised with anionic polyelectrolytes were immobilised on polyester air filters using a layer-by-layer technique. This is the sequential dipping of polyester air filters in a dilute solution of cationic poly(diallyldimethylammonium chloride) and anionic polymeric polyelectrolytes capped silver. The surface topography of the polyester air filters were measured by field emission scanning electron microscope. Results showed that silver nanoparticles had the highest surface coverage on the polyester air filters probably because it is a good bonding candidate and insures strong film growth. The multilayers polyester air filters coated silver nanoparticles were tested against the gram positive pathogen Staphylococcus aureus. The deposition of silver nanoparticles onto the polyester air filters resulted in 92.18%, 84.32% and 71.19% of bacteria removal using PMA, PAA and CoPSS as the stabilising agent.
Keywords: Silver nanoparticle; Zeta potential; Acrylic acid; Layer by layer; Nanoparticles: synthesis and applications